Awareness and Uptake of Maternal and Child Health Benefit Schemes Among the Women Attending a District Hospital in Coastal South India. (March 2020) - Unnikrishnan, Bhaskaran; Rathi, Priya; Sequeira, Renita Maria; Rao, K Kshama; Kamath, Swathi; K., Maria Alfam K.
Abstract: Introduction: Maternal and child health (MCH) benefit schemes were introduced to increase institutional deliveries, to reduce out of pocket expenditure, to provide quality care and nutrition to mother and baby and thereby reduce maternal mortality rate and infant mortality rate. Objective: To assess the awareness and estimate the uptake of benefits regarding various MCH benefit schemes among study participants. Methodology: A cross-sectional study was conducted at district hospital, Mangaluru, Karnataka, India, among 250 antenatal women and postnatal mothers. They were interviewed using a semi-structured–validated questionnaire. Data were analysed using Statistical Package for Social Science version 11.5. Result: Awareness for scheme varied, ranging from 94 per cent for Integrated Child Development Service and 0.8 per cent for Rashtriya Bal Swasthya Karyakram. Major source of information being accredited social health activist (40.41%), most of the study participants had a favourable opinion regarding the benefits of MCH schemes. Maximum uptake was seen for Janani Shishu Suraksha Karyakram (100%); however, none of them availed Prasoothi Araike. Conclusion: Our study showed that the awareness and uptake for different MCH-related schemes varied. Most of the study participants had a favourable opinion about the benefits of MCH schemes. Since awareness for some schemes were low, efforts should be made to increase awareness regarding all schemes by displaying the information. Uptake can be increased by proper channelising the resources.